Biotechnology in agriculture and food processing [ opportunities and challenges - Marwaha, S. S.; Panesar, P. S. [ (Parmjit Singh)] (CRC Press, 2014)
"Preface Biotechnology has a long history of use in agriculture and food processing. It is truly a key technology and has played a significant role in these areas. It represents a combination of both traditional and latest techniques based on molecular biology and recombinant DNA technology. It has not only been helpful in boosting the yield of agricultural crops but has also led to the generation of novel varieties, which can play a significant role in overcoming the problem of hunger and malnutrition worldwide. Biotechnological techniques in food processing offer the prospect of improving existing processes and developing novel products. The applications of biotechnology range from the production of fermented foods to the development of biosensors and food safety kits, which can help ensure the quality and safety of food products. Agriculture and food processing are integrated disciplines, with the latter having its roots in the former. The role of biotechnology in these areas reflects the true picture of its range of applications from "farm to fork." Keeping this in view, the compilation of this volume is expected to provide comprehensive information to the readers on the subject of biotechnology at one platform. The objective of this volume is to provide a perspective on the important biotechnological issues that have direct relevance to agriculture and food processing. Even with restricted perspective, the potential range of the topics is enormous, and it is not possible to review the whole field comprehensively in a single volume. Hence, a careful selection of chapters has been made to provide readers with both an in-depth study and a broad perception"-- Provided by publisher